Pontibacter ramchanderi sp. nov., isolated from hexachlorocyclohexane-contaminated pond sediment - Singh, Amit Kumar; Garg, Nidhi; Sangwan, Naseer; Negi, Vivek; Kumar, Roshan; Vikram, Surendra; Lal, Rup (International Journal of Systematic and Evolutionary Microbiology, 2013)
A Gram-stain-negative, motile, red pigmented, rod-shaped bacterium, designated strain LP43T, was isolated from hexachlorocyclohexane (HCH)-contaminated soil sediment (Lucknow, India). Phylogenetic analysis based on 16S rRNA gene sequences indicated that the isolate formed a cluster with the genus Pontibacter in the phylum Bacteroidetes with sequence similarities ranging from 92.9 to 97.0 % with species of the genus Pontibacter . The DNA G+C content of strain LP43T was 59.1 mol%. The polar lipid profile of strain LP43T showed the presence of phosphatidylethanolamine, an unidentified aminophospholipid, unknown aminolipids and unknown polar lipids. Strain LP43T contained MK-7 as the predominant menaquinone and sym-homospermidine as the major polyamine. The major cellular fatty acids of strain LP43T were, iso-C15 : 0 (15.74 %), iso-C15 : 0 3-OH (7.57 %), iso-C17 : 0 3-OH (7.32 %), summed feature 4 (iso-C17 : 1 I/anteiso-C17 : 1 B) (31.22 %) and summed feature 8 (C18 : 1ω7c/ C18 : 1ω6c) (7.60 %). Based on the results of DNA–DNA hybridization and phenotypic and genotypic characteristics, strain LP43T represents a novel species of the genus Pontibacter , for which the name Pontibacter ramchanderi is proposed. The type strain is LP43T ( = CCM 8406T = MCC 2019T).